Transcatheter edge-to-edge repair of tricuspid valve regurgitation in systemic right ventricle: Echocardiographic outcome - Benadjaoud, Y.; Guérin, P.; Jalal, Z.; Hereau, E.; Le Gloan, L.; Thambo, J.-B.; Iriart, X. (Archives of cardiovascular diseases, 2025)
Transcatheter edge-to-edge repair (TEER) provides an alternative option for high-risk patients with systemic tricuspid regurgitation (STR). Preliminary data of the French study has shown its feasibility and safety, but mid-term echocardiographic outcome is lacking. Echocardiographic outcome of TEER in systemic tricuspid valve regurgitation. Method TEER French cohort is a multicentre, longitudinal, descriptive, prospective study of patients undergoing TEER for severe STR. Fourteen patients with severe or greater STR undergoing percutaneous repair with the MitraClip system were enroled in the study between May 2019 and June 2023. A transthoracic echocardiography was performed at baseline, six months, one year and two years after the procedure. TR was assessed using standard 2-dimensional color Doppler methods and graded TR using the 5-class grading scheme: mild, moderate, severe, massive, and torrential. The number of clips and their localization were analyzed. A reduction of at least 1 grade in TR was achieved in al subjects. TR grade remained moderate or less in 85% of patients at 1-year follow-up, and 83% of patients at 2-years follow-up. TR reduction was sustained at 2-years follow-up for all the 6 patients evaluated. Five patients had one-clip implantation: in the antero-septal coaptation line for 4 patients and in the antero-posterior coaptation line for 1 patient. Nine patients had two or more clips implantation: antero-septal/postero-septal in 2 patients, antero-septal/antero-posterior in 2 patient, 2 antero-septal in 4 patients, 2 antero-septal/antero-posterior in 1 patient. TR grade seemed to be lower in the group of patient with 2-clips strategy at 2-years follow-up: TR was graduated mild in 67% of patients in 2 or more clips group and moderate in 100% of patients in 1-clip group. Systemic tricuspid TEER is found to be safe and effective, with sustained effects at 2 years in patients. Patients with two or more clips implantation seem to have a better outcome in the regurgitation grade, but additional data and a bigger cohort are needed to predict the outcome and define the optimal technical strategy.